Faktor – Faktor yang Mempengaruhi Minat Mahasiswa Memilih Program Studi Pendidikan Ekonomi Universitas Bhinneka PGRI - Roselawati, Anggita; Suryaningsih, Tutut (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to determine the extent to which Internal and external factors affect student interest, the research subjects consisted of 11 active students of the Economic Education study program. This research is a descriptive qualitative research with a case study approach at Bhinneka PGRI University, Tuungagung. Data collection techniques through observation, in-depth interviews and documentation. Analysis techniques with interactive models carried out in four stages, namely: data collection, data display, data presentation, and drawing conclusions. The results of the study showed: Internal factors that influence students' decisions in the Economic Education study program are interest, self-potential, motivation,job opportunities, encouragement from family, the image of the university has a positive impact on students' interest in choosing the Economic Education study program, while social environmental factors and scholarships do not have a significant effect on students' interest. A strategy is needed to improve the image of the study program as an effort to make prospective students interested and confident in choosing the Economic Education study program at Bhinneka PGRI University.